Exercise-induced Rhabdomyolysis in a Young Adult after an Intensive Resistance-circuit Workout: Case Report and Narrative Literature Review - Karol, Michał; Koseska, Kamila; Borowicz, Jan; Górecki, Bartosz; Kloch, Kinga; Romaniuk, Patryk; Lohin, Mariia-Khrystyna; Strawińska, Aleksandra; Bednarczyk, Małgorzata (Quality in Sport, 2026)
Exercise-induced rhabdomyolysis is a potentially serious complication of high-intensity physical activity, increasingly observed in young adults, particularly in the context of high-intensity training, abrupt return to exercise after a longer break, and the widespread use of multi-ingredient pre-workout supplements. Early symptoms are often dismissed as “bad muscle soreness”, which may delay diagnosis and treatment and, in consequence, promote the development of acute kidney injury. The aim of this paper is to present a case of exercise-induced rhabdomyolysis in a young, previously healthy man after a resistance-circuit training session performed following a prolonged period of inactivity, and to discuss current knowledge on the etiology, clinical presentation, diagnostics, treatment and prevention of exercise-induced rhabdomyolysis in young adults. We describe the clinical course, laboratory findings and management, and then relate them to available data, with particular emphasis on environmental factors, dehydration and the use of pre-workout preparations. The case illustrates that early recognition based on simple tests – creatine kinase activity, assessment of kidney function and urinalysis – and prompt initiation of intensive fluid therapy often make it possible to avoid renal replacement therapy. From the perspective of sports medicine and primary care, education of young adults, gradual introduction of training loads, and cautious, informed use of supplements – especially in hot environments and with limited fluid intake – are crucial.